2018
DOI: 10.1021/acs.nanolett.8b02808
|View full text |Cite
|
Sign up to set email alerts
|

Light-Emitting Metasurfaces: Simultaneous Control of Spontaneous Emission and Far-Field Radiation

Abstract: Light-emitting sources and devices permeate every aspect of our lives and are used in lighting, communications, transportation, computing, and medicine. Advances in multifunctional and “smart lighting” would require revolutionary concepts in the control of emission spectra and directionality. Such control might be possible with new schemes and regimes of light–matter interaction paired with developments in light-emitting materials. Here we show that all-dielectric metasurfaces made from III–V semiconductors wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
122
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(123 citation statements)
references
References 40 publications
0
122
1
Order By: Relevance
“…Enhancement of both linear and nonlinear PL by about a factor of eight under one-photon photoexcitation (up to 70 under three-photon photoexcitation) was also observed in metasurfaces based on nanoimprinted perovskite films supporting Mie-like resonances [236]. [159], not taking into account the reduction of the active material due to nanostructuring ( Figure 18B). Yuan et al even found PL enhancements of more than 1000-fold from inverse metasurfaces consisting of arrays of asymmetric holes in a silicon thin film containing Ge QDs [158].…”
Section: Emission Enhancement By Dielectric Metasurfacesmentioning
confidence: 85%
See 1 more Smart Citation
“…Enhancement of both linear and nonlinear PL by about a factor of eight under one-photon photoexcitation (up to 70 under three-photon photoexcitation) was also observed in metasurfaces based on nanoimprinted perovskite films supporting Mie-like resonances [236]. [159], not taking into account the reduction of the active material due to nanostructuring ( Figure 18B). Yuan et al even found PL enhancements of more than 1000-fold from inverse metasurfaces consisting of arrays of asymmetric holes in a silicon thin film containing Ge QDs [158].…”
Section: Emission Enhancement By Dielectric Metasurfacesmentioning
confidence: 85%
“…Using lithographic techniques in combination with reactive ion etching, these wafers can then be nanostructured into the desired nanoantenna or metasurface geometries. This was demonstrated for silicon nanoantennas [157] and metasurfaces [158] containing germanium QDs, as well as for GaAs metasurfaces containing InAs QDs [159]. Alternatively, the fabrication of hierarchical metasurfaces with meta-atoms composed of densely packed QDs in a polymer matrix was also demonstrated [160].…”
Section: Integration Of Emitters With Metasurfacesmentioning
confidence: 98%
“…We believe that asymmetric metasurfaces based on the BIC concept can describe many other phenomena studies earlier with different applications in mind, for example, the electromagnetically induced transparency [158], sensing [159], and light emission control [160].…”
Section: Metamaterials and Metasurfacesmentioning
confidence: 88%
“…E.g., all-dielectric high-Q metasurfaces have recently enabled the ultrasensitive detection of molecular fingerprints and hyperspectral imaging for biosensing without the utilization of spectrometers [26][27][28]. The high-Q metasurfaces were also successfully employed to build novel flat light emitting devices via engineering of spontaneous emission [29,30], stimulated emission [31,32], and nonlinear harmonic generations [33][34][35].…”
mentioning
confidence: 99%